Empowering Resilient Livestock Communities: Sustainable Green Economic Independence - Dedi; Muhammad Abduh; Dede Aji Mardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Ciangir, as a village, part of which is an agricultural area, has potential in developing tough breeders and goat breeders. The aim of this research is to empower the poor-marginalized community who are squeezed due to the condition of the area in the final landfill (TPA). This study used a qualitative descriptive method based on what happened in the field, data collection was carried out through interviews, direct observations, Focus Group Discussion (FGD) and documentation. The selection of informants was carried out using purposive sampling, namely the empowerment of underdeveloped villages, analyzed through an approach using Paticipatory Learning and Action (PLA). This PLA-based approach is an empowerment method that prioritizes community participation in an empowerment process. The PLA method process has a broad impact, because the community is involved, starting from planning, processing and fattening as well as transparent and profitable marketing. The research results show that society in general has the desire and expertise to raise goats, goat farming is resilient to the Covid crisis, demand is high and however hampered by accessibility and capital, people are slowly starting to feel the impact of the rocks being rolled out, such as becoming muzaki and independent breeders and able to move the local community's economy to become more competitive and reduce levels poverty and unemployment.